Entrega Tudo! (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Ifood and/or Art workers must deliver their product to the consumer/spectator within half an hour! Based on this premise and reality, students and the professor of the course Epic Scene Investigation Project, from the Theater Teaching Degree at Unespar, developed fifteen scenes in the play Entrega Tudo! (Deliver Everything!). Seasoned with touches of comedy and Brechtian epic techniques, the group Quadrilha de Piaba, formed through this process, presents the characters: the Delivery Worker, the Presenter, and the Interviewer, intertwined with the antics of the Performers. Through a collectively created dramaturgy, this text aims to explore the daily routine of delivery workers from their homes to receiving and delivering orders through the app.
Keywords: epic theater; Bertolt Brecht; collective creation; dramaturgy